A correspondence analysis of English proficiency and demographic factors among EFL students at Burapha University, Thailand - Pohnsuriya, Piyapohn (Universitas Ahmad Dahlan, 2025)
The study aimed to determine the correspondence association between English proficiency (BUU-CET U Level) and demographic factors of EFL students at Burapha University, Thailand. The sample consisted of 385 non-English major students who took the BUU-CET U exam at Burapha University. Data on BUU-CET U score (level 1-4) and demographic factors were analyzed using descriptive statistics (frequency and percentage) and a correspondence analysis. The results showed that English proficiency, as indicated by the students’ BUU-CET U level, was not associated with gender. The proficiency level 4 tended to associate with the age group of more than 22 years, corresponded most with 5th-year and 6th-year students, and the Health Science faculty group, with a strong association. Students from high-income families tended to have high proficiency at level 4, and students from moderate-income families tended to have moderate proficiency at level 2. According to parents’ education, students whose fathers finished a master’s degree had the most correspondence with the level 4, and students whose mothers obtained a bachelor's degree had the most correspondence with the level 1 and level 3. For parents’ occupation, students whose fathers were freelancers tended to associate closely with level 2, and students whose mothers were housewives had the most correspondence with level 2 and level 4.